An analysis of Scientific Literacy Misconception Using FTT to IPA Teachers in Banda Aceh - Muhammad Azzarkasyi (Jurnal Serambi Ilmu, 2024)
The purpose of this study was to determine the level of misconception using the Four-Tier Test (FTT) for science teachers. Data collection to obtain the required information was carried out using a diagnostic test instrument which was distributed to 29 teachers who were selected as a sample of the total population of science teachers who teach at SMPN in Banda Aceh. To provide an interpretation by differentiating the level of conception of respondents, they are divided into seven categories based on the combination of answers, namely scientific conceptions (SC), misconceptions (MSC), lack of knowledge guessing (LKG), lack of knowledge deficiency (LKD), false positives (FP), false negatives (FN), cannot be encoded (TKD). The test instrument used in the form of Four-Tier Multiple Choice questions as many as 24 items has been equipped with a choice of the Certainty of Response Index (CRI) confidence level along with the reasons for the answer choices. The results showed that scientific conceptions (SC) 30.46%, misconceptions (MSC) 29.74%, lack of knowledge guessing (LKG) 5.32%, lack of knowledge deficiency (LKD) 8.48%, false positives (FP) 13.07%, false negatives (FN) 12.93%.